Therapists’ experiences of remote working during the COVID-19 pandemic - Morgan, Andrew; Davies, Cari; Olabi, Yasmine; Hope-Stone, Laura; Cherry, Mary Gemma; Fisher, Peter (Frontiers in Psychology, 2022)
Objectives To explore the experiences of therapists who delivered remote psychological therapy during the COVID-19 pandemic. Design This was a qualitative, phenomenological study. Interpretative Phenomenological Analysis elicited themes from semi-structured interviews. Methods A purposive sample of eight therapists was recruited from breast cancer services in the United Kingdom. Results Analysis identified three superordinate themes. Participants spoke about how their experience of remote working changed over time from an initial crisis response to a new status quo. They adapted to the specific practical and personal challenges of remote working and struggled to connect with clients as the use of technology fundamentally changed the experience of therapy. Conclusion Consideration should be given to the impact of remote working on therapists and the quality of their practise. Adjustments to ways of working can help to maximize the advantages of remote working while minimizing potential issues.